PENDAMPINGAN PEMBELAJARAN INSPIRATIF MELALUI MEDIA CANVA DAN LIVEWORKSHEET UNTUK GURU DI KOTA PALEMBANG DAN PANGKAL PINANG - Rahmi Susanti,; Safitri, Erna Retna; Sardianto MS,; L.R. Retno Susanti,; Hartono, Hartono; Makmum Raharjo,; Adeng Slamet,; Santi Oktarina, (JURNAL PENGABDIAN MANDIRI, 2022)
Era 4.0 Era 4.0 forces every teacher to constantly improve knowledge and skill competencies in the field of technology so that they can apply them to the learning process. Not yet optimal use of appropriate learning media, limited time to prepare it, difficult to find the right media is still an obstacle to the use of media in learning. One of the media that can be used in developing learning materials is the Canva application and Live Worksheet. This service is expected to be an alternative to solving these problems and increasing the competence of teachers so that they can provide the best learning services for students in the learning process. The purpose of this service is so that teachers can get to know the use of Canva-based media and online Liveworksheets and motivate teachers to diversify the applied learning media. In addition, teachers are also expected to be able to apply and apply it in learning. The method used in this activity is training held with lectures, questions and answers, online practice and mentoring classes. The results of the evaluation showed that after the overall training there was an increase in the average pre-test and post-test scores of 16.6 points from 59.3 to 75.8, which means that the training carried out improved participants' understanding very well. Through the implementation of this community service, teachers can get to know the use of Canva-based media and Liveworksheets, motivate teachers to improve their competencies and make teachers able to apply and implement online-based learning media using the Canva application and Liveworksheet.